Analisis Pengaruh Harga, Kualitas Produk Sepatu Aerostreet Terhadap Kepuasan Pelanggan Yang Membeli di Aplikasi Shopee - Setiyawan, Alan; Waluyo, Edy; Abbas Adika, Muhammad; Paduloh, Paduloh (Jurnal Etnik: Ekonomi-Teknik, 2023)
Shopee is an e-shopping app that concentrates on marketplaces and e-commerce. One of the most popular online shopping apps in Southeast Asia. Aerostreet shoes is a local shoe brand founded by Adhitya Caesarico in Klaten in 2015 and is now the best-selling shoe brand on Shopee. The best-selling Aerostreet shoe products are due to the company often holding massive discounts on Shopee, which reduces product prices and increases sales. Most of the products sold at efficient prices are not always of high quality and cause customer dissatisfaction. The purpose of this study is to determine the influence between customer satisfaction, price and product quality of aerostreet shoes, a total of 39 respondents, aged 17 to 21 years, coming from various professions and having different judgments, were asked to participate in this study. Calculations using the SPSS application, the results of this study indicate that price and customer satisfaction have increased satisfaction in an upward manner while product quality and customer satisfaction have decreased satisfaction in a downward manner because consumers are more tempted by efficient prices than normal prices but guaranteed product quality.